Determinan Pengaruh Kemampuan Auditor dalam Mendeteksi Kecurangan (Studi Empiris di Perwakilan BPKP Provinsi Jawa Tengah) - Meifiani Nur Istiqomah; Jaeni Jaeni; meifiani (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to determine the influence of time pressure, independence, professional skepticism, work experience, professional ethics, and competence on the auditor's ability to detect fraud. Many fraud cases occur in Indonesia, so it is necessary to know the magnitude of the influence of each variable. The population used in this research were auditors who worked at the BPKP Representative Office of Central Java Province. The sample processed by the researcher was 30 respondents. This research uses a questionnaire. This research hypothesis was tested using multiple linear regression analysis with SPSS 22 software. The results of this research show that time pressure, independence, professional skepticism, work experience, professional ethics have no effect on the auditor's ability to detect fraud. while competency has a significant positive effect on the auditor's ability to detect fraud.